Implementing an EMR-based Health-related Social Needs Screen in a Pediatric Hospital System. Issue 1 (January 2022) - Dolce, Millie; Keedy, Hannah; Chavez, Laura; Boch, Samantha; Zaim, Hannah; Dias, Brennan; Chisolm, Deena
Abstract : Introduction: There is growing recognition of the need for effective screening methods and delivering interventions to address health-related social needs (HRSN) in hospital systems, but few studies exist on implementing such a wide-scale undertaking. This article describes the implementation and preliminary findings of a phased roll-out of an institution-wide HRSN screening. Methods: We describe the HRSN implementation and data tracking procedures. Results: During the first 13 months of the roll-out, 62, 315 patient encounters from multiple clinics were eligible for screening, and 52, 331 (84.0%) completed the screening. Twelve percent of patients had at least one HRSN need, and 3.5% of those had an urgent need and thus received a social work consult. Conclusion: Implementation of the first phase of an institution-wide HRSN screen resulted in high screening and follow-up rates among those with urgent needs, demonstrating feasibility across different clinic settings. Abstract : Supplemental Digital Content is available in the text.